Systemic Inflammation Characterizes Lack of Metabolic Health in Nonobese HIV-Infected Men - Monczor, Ana N.; Li, Xiuhong; Palella, Frank J.; Erlandson, Kristine M.; Wiley, Dorothy; Kingsley, Lawrence A.; Post, Wendy S.; Jacobson, Lisa P.; Brown, Todd T.; Lake, Jordan E. (Mediators of Inflammation, 2018)
Background. Increasing body mass index (BMI) is generally associated with loss of metabolic health, although some obese individuals remain metabolically healthy. Among nonobese men, HIV infection has been associated with a lower prevalence of metabolic health. Methods. We conducted a cross-sectional analysis of 470 HIV-infected and 368 HIV-uninfected men enrolled in the Multicenter AIDS Cohort Study Cardiovascular substudy. Circulating biomarker levels were compared by BMI category and by HIV serostatus. Poisson regression with robust variance determined associations between metabolic health and circulating inflammatory biomarker levels after adjusting for factors previously associated with metabolic health. Results. HIV-infected men were younger and less likely to be obese. Among HIV-infected, normal weight metabolically healthy men (compared to unhealthy) had significantly lower circulating levels of interleukin- (IL-) 6, soluble tumor necrosis factor receptors (sTNFR) I and II, and homeostatic model assessment of insulin resistance (HOMA-IR), higher adiponectin, less visceral fat, and more subcutaneous fat. Among HIV-uninfected normal weight men and obese men (regardless of HIV serostatus), metabolic health was associated only with higher levels of adiponectin, less visceral fat, and lower HOMA-IR values. In multivariate analyses restricted to HIV-infected men, lower hs-CRP, sTNFRI, sTNFRII, and HOMA-IR and higher adiponectin levels were associated with metabolic health. Additional adjustment for visceral adiposity did not alter results. Conclusions. Among HIV-infected normal weight men, metabolic health was associated with less systemic inflammation, a relationship that, among normal weight men, was unique to HIV+ men and did not exist among obese men of either HIV serostatus.